Primary students’ argumentation skills on evaporation: A teaching intervention - Angeloudi, Anastasia; Papageorgiou, George (Preschool and Primary Education, 2022)
This paper reports the findings of a study exploring the possibilities of improving students’ argumentation skills concerning evaporation process and factors affecting evaporation by implementing two teaching schemes, with and without the use of particle theory. The participants (ages 10/11, n = 77) were students of four fifth-grade classes of two Greek regular public primary schools. The research data were collected through an open-ended written test (pre- and post-intervention) and a semi-structured interview (post-intervention). Results revealed that the improvement of students’ argumentation skills regarding the evaporation process and the factors affecting evaporation is feasible through an appropriate teaching intervention. This concerns mainly the components of claim and evidence, whereas the use of the particle theory seems to contribute further to this improvement, as well as to the improvement of the reasoning component. Implications for science education are also discussed.